Сучасні методи визначення гранулометричного складу осадових порід та особливості їх застосування - Стадніченко, С.М. (Інститут геологічних наук НАН України, 2009)
Размер частичек и гранулометрический состав осадочных пород и грунтов являются ключевыми характеристиками в литологии и инженерной геологии. Эти параметры определяют механические свойства пород, а также дают информацию о процессах разрушения, способах переноса и условиях осадконакопления. В данной статье рассмотрены методы исследования гранулометрического состава осадочных пород, которые основываются на разных физических принципах: скорости осаждения частиц, лазерной дифракции, электропроводимости частичек, анализе изображения и т.д. При рассмотрении данных методов представлены такие критерии: диапазон размера измеряемых частичек, размер навески образца, скорость анализа, сложность процедуры измерения, обработка результатов, повторяемость результатов. Установлены основные критерии выбора оптимального метода определения гранулометрического состава в зависимости от типа пород и специфики задачи исследований. Grain-size and grain-size distribution of sedimentary rocks and soils are key factors in sedimentology and engineering geology. These parameters determine the mechanical properties of sediment and provide information on the origin and history of the latter; they also determine by which agent sediment can be eroded, in which physical mode it will be transported, and how it will be deposited. Several techniques and instruments for measuring the grain-size distribution of sedimentary rocks are represented in this comparative study, based on: sedimentation, image analysis, laser diffraction, electroresistance particle counting and other. An appropriate evaluation thus requires that various criteria be considered. Issues to be taken into account are: type of sediment, quantity of sediment available, speed of measurement, complexity of the measurement protocol, processing of the data, reproducibility of the results and the specific aims of the study undertaken. The choice of a optimum technique thus depends on the type of sediment and the specific aims of the study undertaken.